1999
DOI: 10.1126/science.286.5446.1937
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Evidence for an Arctic Sea Ice Cover in Transformation

Abstract: Recent research using microwave satellite remote sensing data has established that there has been a reduction of about 3 percent per decade in the areal extent of the Arctic sea ice cover since 1978, although it is unknown whether the nature of the perennial ice pack has changed. These data were used to quantify changes in the ice cover's composition, revealing a substantial reduction of about 14 percent in the area of multiyear ice in winter during the period from 1978 to 1998. There also appears to be a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
205
2
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 352 publications
(226 citation statements)
references
References 25 publications
15
205
2
4
Order By: Relevance
“…Barnett et al (2001) calculated, with confidence exceeding 95%, that human-produced greenhouse gases are responsible for the horizontal and temporal character of the observed increase in ocean temperature. The aerial extent of arctic ice has declined by as much as 7% per decade over the last 20 years (Johannessen et al 1999) and thinned by as much as 15% per decade (Rothrock et al 1999). While this may be related to a decadal-scale mode of Arctic atmospheric variability, comparisons with GeM outputs suggest that the declines are related to anthropogenically-induced global change (Vinnikov et al 1999).…”
Section: Ocean Temperature and Ice Extentmentioning
confidence: 96%
“…Barnett et al (2001) calculated, with confidence exceeding 95%, that human-produced greenhouse gases are responsible for the horizontal and temporal character of the observed increase in ocean temperature. The aerial extent of arctic ice has declined by as much as 7% per decade over the last 20 years (Johannessen et al 1999) and thinned by as much as 15% per decade (Rothrock et al 1999). While this may be related to a decadal-scale mode of Arctic atmospheric variability, comparisons with GeM outputs suggest that the declines are related to anthropogenically-induced global change (Vinnikov et al 1999).…”
Section: Ocean Temperature and Ice Extentmentioning
confidence: 96%
“…This includes, inter alia, connections with the North Atlantic Oscillation (e.g., Hurrell and van Loon, 1997;Johannessen et al, 1999;Kwok and Rothrock, 1999;Deser et al, 2000;Kwok, 2000;Vinje, 2001); the spatially broader Arctic Oscillation (e.g., Deser et al, 2000;Wang and Ikeda, 2000); the Arctic Ocean Oscillation Proshutinsky et al, 1999); the "see-saw" in winter temperatures observed between Greenland and northern Europe (Rogers and van Loon, 1979); and an interdecadal Arctic climate cycle (Mysak et al, 1990;Mysak and Power, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…• Johannessen et al (1999) analyzed Arctic sea ice extent over the period and found it to have decreased by about 14 percent. The change occurred rather abruptly over a single period of not more than three years (1987/88-1990/91) and possibly only one year (1989/90-1990/91).…”
Section: Earlier Researchmentioning
confidence: 99%
“…The question of long-term thinning, redistribution and retraction of Arctic Sea-ice has been extensively discussed in the literature for example, Rothrock et al (1999), Johannesen et al (1999), Wadhams and Davis (2000), Holloway and Sou (2002), Laxon et al (2003), Rothrock et al (2003), Comiso (2002) and Sroeve et al (2005). The most recent of these (Stroeve et al) shows that the downward trend in ice extent at the annual minimum (September) has been À7.7 ± 3% per decade since 1979 with evidence of a reinforced downturn in the most recent years.…”
Section: Arctic Ocean Sea-icementioning
confidence: 99%